Identification of Neuronal Pentraxins as Synaptic Binding Partners of C1q and the Involvement of NP1 in Synaptic Pruning in Adult Mice - Kovács, Réka Á.; Vadászi, Henrietta; Bulyáki, Éva; Török, György; Tóth, Vilmos; Mátyás, Dominik; Kun, Judit; Hunyadi-Gulyás, Éva; Fedor, Flóra Zsófia; Csincsi, Ádám; Medzihradszky, Katalin; Homolya, László; et al. (Frontiers in Immunology, 2021)
Elements of the immune system particularly that of innate immunity, play important roles beyond their traditional tasks in host defense, including manifold roles in the nervous system. Complement-mediated synaptic pruning is essential in the developing and healthy functioning brain and becomes aberrant in neurodegenerative disorders. C1q, component of the classical complement pathway, plays a central role in tagging synapses for elimination; however, the underlying molecular mechanisms and interaction partners are mostly unknown. Neuronal pentraxins (NPs) are involved in synapse formation and plasticity, moreover, NP1 contributes to cell death and neurodegeneration under adverse conditions. Here, we investigated the potential interaction between C1q and NPs, and its role in microglial phagocytosis of synapses in adult mice. We verified in vitro that NPs interact with C1q, as well as activate the complement system. Flow cytometry, immunostaining and co-immunoprecipitation showed that synapse-bound C1q colocalizes and interact with NPs. High-resolution confocal microscopy revealed that microglia-surrounded C1q-tagged synapses are NP1 positive. We have also observed the synaptic occurrence of C4 suggesting that activation of the classical pathway cannot be ruled out in synaptic plasticity in healthy adult animals. In summary, our results indicate that NPs play a regulatory role in the synaptic function of C1q. Whether this role can be intensified upon pathological conditions, such as in Alzheimer’s disease, is to be disclosed.